2003
DOI: 10.1161/01.res.0000054625.24468.08
|View full text |Cite
|
Sign up to set email alerts
|

Depletion of Intracellular Ca 2+ Stores Sensitizes the Flow-Induced Ca 2+ Influx in Rat Endothelial Cells

Abstract: Abstract-Hemodynamic shear stress elicits a rise in endothelial [Ca 2ϩ ] i , which may serve as a key second messenger to regulate many flow-associated physiological and biochemical processes. In the present study, we used Mn 2ϩ quenching of fluorescent dye Fluo3 as an assay to investigate the Ca 2ϩ influx of rat aortic endothelial cells in response to flow. We found that the Ca 2ϩ signaling in response to flow could be greatly influenced by the status of intracellular Ca 2ϩ stores. Depletion of intracellula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
58
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(64 citation statements)
references
References 35 publications
6
58
0
Order By: Relevance
“…Similar feedback inhibition has been well documented in vascular endothelial cells. [25][26][27] In this feedback mechanism, Ca 2+ influx would stimulate a nitric oxide-cGMP-PKG cascade, resulting in a negative feedback inhibition on Ca 2+ entry channels (i.e., heteromeric TRPV4-P2 channels in this case). The following sets of data support this notion: (1) ] i transients more sustained.…”
Section: Discussionmentioning
confidence: 99%
“…Similar feedback inhibition has been well documented in vascular endothelial cells. [25][26][27] In this feedback mechanism, Ca 2+ influx would stimulate a nitric oxide-cGMP-PKG cascade, resulting in a negative feedback inhibition on Ca 2+ entry channels (i.e., heteromeric TRPV4-P2 channels in this case). The following sets of data support this notion: (1) ] i transients more sustained.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism whereby the cell detects and responds to the mechanical stimulus is unclear, but there are two (not mutually exclusive) possibilities that have gained some biological evidence. One is the existence of Ca 2 + channels in the plasma membrane that are directly gated by shear stress (Kwan et al, 2003); the second is a shear-sensitive mechano-receptor that is linked to the IPa signalling pathway (Tseng et al, 1995). However, very few data exist regarding mechano-transduction via IPa in EC, so we focus on the first of these mechanisms.…”
Section: Model For Endothelial Calcium Dynamicsmentioning
confidence: 99%
“…Depletion of the internal stores appears to stimulate influx of Ca 2 + into the cell via plasma membrane ion channels (a process known as capacitative Ca 2 + entry) (Putney et al, 2001), and can also accelerate the rate of release of Ca 2 + from the ER into the cytosol (Ca 2 +-induced Ca 2 + release) (Wood and Gillespie, 1998). Wall shear stress appears to contribute to Ca 2 + signalling by activating plasma membrane Ca 2 + channels, thus allowing further influx (Kwan et al, 2003). Wall shear stress may also activate a mechano-sensitive surface receptor linked to the IP3 signalling pathway, thus increasing the rate of internal Ca 2 + release (Tseng et al, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…A key issue for all forms of CC is whether the direct physical link that conveys mechanical conformational energy from one protein to another can also act as a pathway to either focus applied mechanical forces on the channel or alternatively constrain the channel from responding to mechanical forces generated within the bilayer. Another possibility is that reorganization or clustering of the resident ER protein (i.e., STIM) that senses Ca 2+ stores may alter channel mechanosensitivity by increasing the strength of CC (Kwan et al 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have already implicated TRPC1 in regulating cell migration. For example, Huang et al (2003) showed immunohistologically that TRPC1 was expressed in a punctuate pattern around the cell periphery, and based on Gd 3þ block proposed that TRPC1 supported [Ca 2þ ] i transients and cell migration. while studying an intestinal epithelial cell line demonstrated that suppression of TRPC1 inhibited cell migration, whereas TRPC1 overexpression of TRPC1 enhanced cell migration as measured by an in vitro wound closure assay.…”
Section: Mscca and Metastasismentioning
confidence: 99%